Osteoporotic profiles in elderly patients with symptomatic lumbar spinal canal stenosis - Lee, Byung Ho (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The osteoporosis and lumbar canal stenosis, in elderly patients are under diagnosed and under reported. We report a cross sectional study to demonstrate the osteoporotic profile in patients with lumbar spinal stenosis (LSS) and to determine the proportion of patients with LSS who need to be treated for osteoporosis. MATERIALS AND METHODS: One hundred and six postmenopausal patients with symptomatic LSS were evaluated for osteoporotic profile, which included lumbar and hip bone mineral density (BMD), serum vitamin D concentration, bone resorption and formation markers. Demographic and disease related variables were analyzed to identify the association with the risk of osteoporosis or osteopenia. Statistical analysis used were multivariate logistic regression with a forward stepwise procedure. RESULTS: Twenty-four patients (22.6%) had osteoporosis and 60 (56.6%) had osteopenia. Overall, 84 patients (79.2%) with symptomatic LSS had osteoporosis or osteopenia. Fifty-nine patients (55.6%) had hypovitaminosis D. All bone turnover makers [alkaline phosphatase, osteocalcin, urinary-N-terminal telopeptide (u-NTx)] were demonstrated to be within normal range. Only age was associated with the risk of osteoporosis or osteopenia in the hip region. In the lumbar spine, all variables were not associated with osteoporosis or osteopenia. 44 patients (41.5%) required treatment for osteoporosis as per risk factors for osteoporosis. According to the guidelines from the Health Insurance Review Agency, however, only 20 patients (18.8% required) qualified for reimbursement for osteoporosis medications. CONCLUSIONS: LSS is associated with osteopenia, osteoporosis, and hypovitaminosis D, which should prompt careful screening and treatment in cases of osteoporosis and osteoarthritis.